The Dynamics of Digital Transformation in Celuk Village: Opportunities, Challenges, and Readiness - Rukmawati, DIah; Pradnyana, I Putu Hadi (Universitas Pancasakti, 2024)
This research aims to analyze the dynamics of digital transformation in Celuk Village with a focus on opportunities, challenges and village readiness in adopting digital technology. Using the Technology Acceptance Model (TAM) framework, this research evaluates perceived usefulness (PU), ease of use (Perceived Ease of Use/PEOU), attitudes towards using technology (Attitude Toward Using Technology), behavioral intentions to use technology (Behavioral Intention to Use Technology), and actual use of technology in the context of digitalization of village government. Research findings show that the Celuk Village Government has started a digitalization initiative by developing a village website that provides information and catalogs of silver crafts. This website is considered a significant first step in increasing the transparency and accessibility of information. However, digital administrative services are still in the development stage and have not been fully implemented. The main opportunity lies in the relatively high readiness of village officials' human resources (HR) in adopting technology, as well as basic infrastructure such as public Wi-Fi that supports access to digital information. Village communities also show a fairly good level of digital literacy, especially in the context of using technology to promote local products.